2014
DOI: 10.1177/1559827613520120
|View full text |Cite
|
Sign up to set email alerts
|

The Evidence in Support of Physicians and Health Care Providers as Physical Activity Role Models

Abstract: Physical inactivity constitutes the fourth leading cause of death worldwide. Health care providers (HCPs) should play a key role in counseling and appropriately referring their patients to adopt physical activity (PA). Previous reports suggest that active HCPs are more likely to provide better, more credible, and motivating preventive counseling to their patients. This review summarizes the available evidence on the association between HCPs’ personal PA habits and their related PA counseling practices. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
165
2
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(187 citation statements)
references
References 80 publications
9
165
2
11
Order By: Relevance
“…The deeper insight into their own health and health habits physicians gain, the more realistic and effective their advice to patients will be (28). In general, health professionals' own alcohol use may also play an important role in their interaction with their patients (22;29).…”
Section: Physical Inactivity Among Healthcare Workersmentioning
confidence: 99%
“…The deeper insight into their own health and health habits physicians gain, the more realistic and effective their advice to patients will be (28). In general, health professionals' own alcohol use may also play an important role in their interaction with their patients (22;29).…”
Section: Physical Inactivity Among Healthcare Workersmentioning
confidence: 99%
“…Consistent evidence revealed that physically active physicians and other HCPs are more likely to provide PA counseling to their patients and can indeed become powerful PA role models [16]. Physical inactivity prevalence in Ethiopia is not well known, since there is no sufficient research regarding to this area.…”
Section: Introductionmentioning
confidence: 99%
“…Sus propios estilos de vida influirán en sus labores profesionales y en el alcance que tengan las recomendaciones que brinden a sus pacientes para motivarlos a realizar cambios positivos (Duperly et al, 2009;Shai et al, 2012;Fie, Norman & While, 2012;Lobelo & de Quevedo, 2014). Idealmente, debería existir un trabajo conjunto entre profesionales de medicina y profesionales del movimiento humano.…”
Section: Discussionunclassified
“…Las y los médicos desempeñan un papel preponderante en la prevención primaria del sobrepeso, la obesidad y los hábitos inadecuados de alimentación, por lo tanto fungen como modelos sociales y sus propias prácticas impactan negativa o positivamente su credibilidad ante los pacientes (Lobelo & de Quevedo, 2014;Fie, Norman & While, 2012). El tabaquismo en médicos y la relación de este hábito con la práctica profesional también ha sido objeto de estudio en años recientes (Duaso, McDermott, Mujika, Purssell & While, 2014).…”
unclassified